Konflik Agraria Di Pedesaan, Tantangan Dan Harapan : Studi Desa Bingkawan-Rambung Baru Kab.Deli Serdang - Latifah Hannum Gultom; Ardilla Sulvina; Febriana Febriana; Putri Andini; Salsabila Balqis; Saparutdin Brutu; Ramsul Nababan (Student Research Journal, 2023)
In Indonesia, land or agrarian issues usually confront local communities with the power of capital or corporations and state instruments. If we look back, land problems usually start from monopoly policies on land ownership by the state and are then commercialized by the state to gain profits, which is still very difficult to resolve. Providing proof of ownership of land, or a land title certificate, is a way to organize assets in this case. On the other hand, managing access means providing support or infrastructure, such as infrastructure, market support, capital, technology and other assistance, so that the subject of Agrarian Reform can develop. The method used in this research is a descriptive method with a literature approach. Literature study is defined as a series of activities related to collecting information relevant to the topic or problem that will be or is being researched from library sources, reading, taking notes and processing research materials. Thus, this article aims to provide a deeper understanding of agrarian conflict in rural areas, challenges and hopes (Bingkawan-Rambung Baru Village Study, Sibolangit subdistrict, Deli Serdang district).